Effect of two different types of Olympic rotation order on cardiovascular and metabolic variables in men`s artistic gymnastics - Mkaouer, B.; Jemni, M.; Chaabene, H.; Amara, S.; Njah, A.; Chtara, M. (Journal of Human Kinetics, 2018)
The rotation sequence-order differs from a gymnast to another according to the draw at the time of the qualifying competitions in men`s artistic gymnastics. Only the six best gymnasts start on the floor exercises, the others could start on any of the other five apparatuses. It has been demonstrated that some gymnastics events are physiologically less taxing than others; hence some gymnasts could experience lower and/or higher levels of cardiovascular and metabolic stress compared to others, depending on the apparatus they start with. In this regard, the objective of this investigation was to compare cardiovascular and metabolic variables between two different types of Olympic rotation-order; one began with the floor exercises and the other began with the pommel horse. Six elite male gymnasts took part in this investigation. Heart rates, synchronized with real-time video acquisition, as well as capillary lactate concentration following each apparatus routine were monitored. Cardiovascular and metabolic stresses were significantly higher when gymnasts started their rotation with the pommel horse in all apparatuses except the pommel horse. The floor exercises` score was significantly affected when gymnasts ended up their competition on this apparatus. As a conclusion, starting gymnastics` competition on the floor exercises implicates less cardiovascular and metabolic stress associated with better performance compared with the other rotation order. As a matter of fact, best gymnasts who start on this apparatus could have a slight advantage compared with the other athletes.